Enhancing service quality and job satisfaction: a framework for transformational leadership in higher education context / Chaoyi Zhang, Donnie Adams and Ahmad Zabidi Abdul Razak - Zhang, Chaoyi; Adams, Donnie; Abdul Razak, Ahmad Zabidi (Universiti Teknologi MARA, 2024)
Leaders practicing transformational leadership tend to have more committed and satisfied employees as they motivate employees to do more, and support their personal development. However, little is known about the relationships among transformational leadership, job satisfaction, and service quality in the higher education context. The purpose of this paper was to propose a conceptual framework on the mediating effect of job satisfaction on the relationship between transformational leadership and service quality based on past research, particularly in the higher education context. The proposed conceptual framework was developed based on a literature review on transformational leadership, job satisfaction, and service quality. Findings suggested that transformational leadership positively influences service quality via the mediating effect of job satisfaction in the higher education context. By proposing that transformational leadership affects service quality via job satisfaction, this study’s proposed framework lays a strong foundation for the expansion of the transformational leadership knowledge base as well as for future theory development and debate.